2015
DOI: 10.1371/journal.pone.0130697
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Estimates of Crude and Effective Coverage of Measles Immunization in Low-Resource Settings: Findings from Salud Mesoamérica 2015

Abstract: Timely and accurate measurement of population protection against measles is critical for decision-making and prevention of outbreaks. However, little is known about how survey-based estimates of immunization (crude coverage) compare to the seroprevalence of antibodies (effective coverage), particularly in low-resource settings. In poor areas of Mexico and Nicaragua, we used household surveys to gather information on measles immunization from child health cards and caregiver recall. We also collected dried bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…In any setting with delays in vaccination, 'up-to-date coverage' will be a biased measure of vaccination-induced population immunity (38) and this bias, always over-estimating protection, can be as great as 24% in our survey. (38)(39)(40) AUC is a better measure because it provides an estimate of mean vaccination coverage throughout the period of risk. However, true population immunity will be lower than the AUC because a small proportion of vaccinated children will not develop an appropriate antibody response either because of operational factors (ineffective administration, inactive vaccine, heat destroyed vaccine, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…In any setting with delays in vaccination, 'up-to-date coverage' will be a biased measure of vaccination-induced population immunity (38) and this bias, always over-estimating protection, can be as great as 24% in our survey. (38)(39)(40) AUC is a better measure because it provides an estimate of mean vaccination coverage throughout the period of risk. However, true population immunity will be lower than the AUC because a small proportion of vaccinated children will not develop an appropriate antibody response either because of operational factors (ineffective administration, inactive vaccine, heat destroyed vaccine, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Oral fluid performed well in studies in Ethiopia and Kenya but poorly in Bangladesh . A study using DBS in poor areas of Mexico and Nicaragua found very low measles antibody prevalence (68% and 50%, respectively) despite high reported vaccination coverage and successful measles elimination in both countries . Although the study showed internal consistency in that antibody prevalence was lowest in areas with known cold chain or vaccination recording problems, it is hard to reconcile this low prevalence with the absence of measles outbreaks.…”
Section: Discussionmentioning
confidence: 90%
“…In settings where infections are eliminated or near elimination and there are very few disease notifications, serosurveillance can detect immunity gaps before outbreaks occur. Causes of immunity gaps include failure to vaccinate certain population groups , in‐migration of unvaccinated persons , reduced vaccine effectiveness or waning vaccine‐induced immunity . Ideally, immunity gaps are identified in time to prevent outbreaks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, equipment is required, as described by Scobie et al (15) and others (27), to maintain a reverse cold/freeze chain. The use of dried blood spots (DBS) does not obviate a needle stick but does eliminate the requirement for a cold/freeze chain (28,29). However, once back in the reference laboratory the DBS must undergo a cumbersome elution step to obtain quasiserum for testing.…”
mentioning
confidence: 99%